Metal Metabolism in Animals - Reinhard Dallinger (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Through evolution of life, animals have adapted to the ubiquitous presence of metals in the biosphere. They utilize the more frequent ones as essential constituents of their biochemical machinery. In fact, about 40% of all proteins present in animal cells are so-called metalloproteins. On the other hand, animals have invented regulatory and detoxifying mechanisms to protect themselves from critical concentrations of both essential and non-essential metal concentrations. Metallomics is a modern approach applying cellular, biochemical, molecular and analytical methods to investigate the relationships of metals in their cellular context. The present edition contains a number of original articles and reviews dealing with various aspects of metallomics in animals, published as Special Issues of the International Journal of Molecular Sciences in 2016 and 2017. The book addresses subjects such as metal definition in biology, metabolism of metals in invertebrate and vertebrate animals, metal detoxification and regulation strategies, supplementation of essential trace elements, metal behavior in pregnancy and embryonic development, as well as metal toxicology and emerging medical implications.